Synchronizing Environmental Education Research Trends: Promoting Sustainable Practices and Enhancing Scientific Knowledge - Ali, M. Ichsan; Arfandi, Anas (International Journal of Environment, Engineering and Education, 2024)
This research explores the diversity of topics related to environmental education issues and students’ environmental concerns regarding their behavior. The bibliometric method is a quantitative approach used to measure and investigate specific indicators within the literature published in a particular field. This method involves creating knowledge maps using extensive databases to identify patterns and trends. Using the keyword “environmental education” on Scopus from 2018 to 2023, 365 relevant documents were found. In the PRISMA flow diagram, the process started with 7550 traced documents, narrowing down to 2536 relevant documents through screening. From these, 776 related documents were chosen, and 573 relevant documents were recognized after the inclusion stage. Throughout, a total of 365 publications were included in the study. VOS viewer software was used to analyze data and generate bibliographic maps and networks. In the last five years, research on environmental education has experienced exciting fluctuations. Key sources like Sustainability Switzerland and the International Journal of Environmental Research and Public Health have played a significant role. Research by Bogner, F.X. stands out, reflecting high interest in environmental issues and education within the scientific community. Universities such as Universidad de Granada and Universiti Kebangsaan Malaysia contribute significantly. The United States leads in publications. Environmental education research remains crucial for sustainable practices and environmental literacy despite fluctuations. This data provides essential guidance for future research planning. This research not only underscores the increasing research emphasis on the educational ramifications of pandemics but also identifies specific areas that warrant more extensive exploration.